Pengaruh Sikap Keuangan, Kontrol Diri dan Self Reward Terhadap Pengelolaan Keuangan pada Generasi Z di Kecamatan Telukjambe Barat - Maya Komala; Sihabudin; Robby Fauji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the effect of financial attitude variables, self-control and self-reward on financial management. Furthermore, this research also aims to identify the factors that have the greatest effect on financial management. This study used a verifiative descriptive method. The sampling technique is purposive sampling and uses the Slovin formula. The study was conducted using a Likert scale questionnaire distributed via Google Form to 100 Generation Z respondents in West Telukjambe District. Data analysis techniques use path analysis and simultaneous and partial hypothesis testing. The results of this study showed a positive correlation between variables X1 and X2, X1 and X3, and X2 and X3. Partially, financial attitudes have a positive and significant influence on financial management. Self-control has a positive and partially significant effect on financial management, while self-reward has a partial negative and significant effect on financial management. Then, variables such as financial attitude, self-control and self-reward also has a significant simultaneously on financial management.